Strategi Digital Marketing dalam Meningkatkan Daya Saing Pelaku Ekonomi Kreatif : Studi Kasus pada Usaha Kain Tenun Bali Dewi di Singaraja - Dewi, Ni Putu Sthira Sattwika; Suwendra, I Wayan (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze and formulate the right digital marketing strategy to increase the competitiveness of creative economy actors, especially in the traditional woven cloth business